Pemaknaan Lagu â€œLir-Ilirâ€ Karya Sunan Kalijaga Sebuah Analisis Semiotik Saussure - nikendwipuspitasari (Madah: Jurnal Bahasa dan Sastra, 2024)
The purpose of this research is to reveal the real meaning behind the lyrics of the song "lir Ilir" by Sunan Kalijaga. This is important because the song is considered by some as a sign that the "physical resistance" of Muslims during the 14th century AD against the hegemony of Hindu power has begun. In fact, in several studies on the beginning of Islam in the archipelago, it is always stated that Islam entered the archipelago in a "peaceful way". This research uses qualitative method with Saussure's semiotic approach. Meanwhile, the material object of this research is the lyrics of the song "lir ilir" by Sunan Kalijaga, while the formal object is Saussure's semiotics. Saussure's theory can explain that language is a sign system in which there are signifiers and signifieds. Of course, this process relates to song lyrics and the real world. The result of this research is that the lyrics of the song "lir Ilir" have the meaning of awakening which means that the lyrics of the song are intended to arouse the spirit and focus in worship so that it can form the souls of true leadership. In addition, so that humans are free from laziness so that they can become good humans, namely humans who can provide benefits to other humans.